PROFESI BIMBINGAN DAN KONSELING DALAM MASYARAKAT - Hasan Baharudin, Yusuf (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2021)
The title of this journal writing is expected to answer the formulation of the problem of how the profession guidance counseling in the community. Based on these issues the journal discusses the concept of counseling, community concepts and the implications of the counseling profession profession in the community. The method that writer use in this research is library method This journal title is expected to answer to society related to counseling in society. Especially about the implications of the profession counseling guidance in the community can be done by providing counseling services that are as a helper profession or social worker. The result of the discussion of this journal is counseling as a profession counseling community (profession counseling comunity) is a concept that underlies the role and funsi counselors in today's society. In line with the dynamics of life, the need for guidance and counseling is not only felt in the school environment. Currently, counseling services are being developed in a broader set of societies in which there are families, careers, the elderly and other societies so that counseling in the community is urgently needed.